Students’ Perception on Peer-Video Recording Task in the Vocational High School in Cirebon - Khumaeroh, Rubia'tul; Dwiniasih (Institut Agama Islam Negeri Madura, 2024)
The purpose of this study is to investigate whether the implementation of the peer-video recording task assists EFL students in developing their speaking skills. Tenth-grader students in vocational high school were involved in this research. The data was collected through questionnaires and interviews. The results revealed that students have a positive perception toward the implementation of the peer-video recording task in speaking class due to its benefits in improving students’ speaking performance, such as pronunciation and fluency. Nevertheless, the peer-video recording task was perceived as neutral by students in terms of boosting self-confidence, its convenience in recording the video with their partner, the ease of speaking in pairs, and promoting students’ autonomous learning. Notwithstanding those results, peer-video recording tasks are effective teaching and learning tools for teaching speaking.